2017
DOI: 10.1083/jcb.201607093
|View full text |Cite
|
Sign up to set email alerts
|

A Drosophila model of Fragile X syndrome exhibits defects in phagocytosis by innate immune cells

Abstract: Recent evidence suggests that Fragile X syndrome and other types of autism are associated with immune system defects. Here, O’Connor et al. find that Drosophila Fmr1 mutants, a model for Fragile X syndrome, exhibit defects in phagocytosis by innate immune cells in both the body and the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 49 publications
(68 reference statements)
0
37
0
Order By: Relevance
“…For example, in the antennal lobe of Drosophila the morphology and connectivity of local interneurons can vary between animals and may require NG to respond accordingly (Chou et al, 2010). Finally, NG may also play an important role in maintaining axons and in monitoring and pruning synapses to ensure the proper number and type of synaptic connections, as they do in invertebrates (O’Connor et al, 2017) and vertebrates (Risher et al, 2014), respectively, during normal development and after injury (Burda et al, 2016; He and Jin, 2016; Stephan et al, 2012). Glial developmental plasticity may be essential to achieve robustness and maintain homeostasis by readily adapting to these and perhaps other variations in nervous system size and morphology.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the antennal lobe of Drosophila the morphology and connectivity of local interneurons can vary between animals and may require NG to respond accordingly (Chou et al, 2010). Finally, NG may also play an important role in maintaining axons and in monitoring and pruning synapses to ensure the proper number and type of synaptic connections, as they do in invertebrates (O’Connor et al, 2017) and vertebrates (Risher et al, 2014), respectively, during normal development and after injury (Burda et al, 2016; He and Jin, 2016; Stephan et al, 2012). Glial developmental plasticity may be essential to achieve robustness and maintain homeostasis by readily adapting to these and perhaps other variations in nervous system size and morphology.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no other published work links FMRP and Shrub. However, a recent study demonstrates FMRP regulates synaptic pruning of MB neurons (downstream of PNs) during metamorphosis 69 , a process where Shrub has a pivotal role 26 28 . Likewise, the well-studied neuromuscular junction (NMJ) model synapse shows A-D modulation 70 , with established roles for FMRP 11 , 15 and Shrub 24 modulating connectivity during embryonic and larval development.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it may be envisioned that reduced chemokine levels in FXS patients may be associated with a reduced capacity of the immune system of FXS patients to respond to specific pathogens. Of note, one study in the Drosophila melanogaster model of FXS showed that the dfmr1 mutants exhibit increased sensitivity to bacterial infection and decreased phagocytosis of bacteria by systemic immune cells [29], suggesting that dfmr1 gene is required for the activation of phagocytic immune cells and therefore for their immune responsiveness.…”
Section: Reduced Levels Of Pro-inflammatory Chemokines In Fxs Patientsmentioning
confidence: 99%